Analisis Kepatuhan Atas Implementasi Akuntansi Perpajakan Pada Kantor Badan Pengelolaan Keuangan Dan Aset Daerah Kabupaten Bogor - Pratama, Andikha Putra; Rahmat Mulyana Dali; Yudiana (CV. ITTC INDONESIA, 2024)
The research in this thesis aims to determine and analyze tax accounting compliance such as withholding and/or collection, depositing and reporting taxes at the BPKAD office of Bogor Regency in accordance with applicable regulations. This research uses a quantitative descriptive method, the data collection technique used is documentation obtained directly from the expenditure treasurer. The findings of this study indicate that the level of compliance in calculating and depositing taxes in 2022 and 2023 is 100%, while the level of compliance in tax reporting is still not optimal as seen from the compliance of tax reporting in 2022 of 81.82% and in 2023 of 91.67%. The results of this study indicate that the level of tax compliance at the BPKAD office of Bogor Regency is high but still not in accordance with the Minister of Finance Regulation Number 59 / PMK.03 / 2022 with this the author can conclude that the implementation of tax accounting at the BPKAD office of Bogor Regency is still not optimal.